Communicative language teaching: Structure-Based or Dynamic Usage-Based?. Issue 1 (12th July 2022) - Rousse-Malpat, Audrey; Steinkrauss, Rasmus; Wieling, Martijn; Verspoor, Marjolijn
Although communicative language teaching (CLT) was thought to have revolutionized classroom practice, there are "weak" and "strong" versions (Howatt, 1984 ). Most foreign language classrooms in the world still favor weak versions with structure-based (SB) views on language (Lightbown & Spada, 2013 ), and practice in the Netherlands is not much different (West & Verspoor, 2016 ). However, a small group of teachers in the Netherlands started teaching French as a second language with a strong CLT program in line with Dynamic Usage-Based (DUB) principles. Rather than focusing on rule learning and explicit grammar teaching to avoid errors, the DUB program takes the dynamics of second-language development into consideration and focuses on the three key elements of usage-based theory: frequency, salience and contingency. These translate into a great deal of exposure, repetition, learning the meaning of every single word through gestures, and presenting whole chunks of language, all without explicit grammar teaching. This study aims to compare the effects of the SB and DUB instructional programs after three years. We traced the second-language development of 229 junior high school students (aged 12 to 15) learning French in the Netherlands over three years. The participants took three oral tests over the course of three years (568 interviews) and wrote seven narratives on the same topic (1511 narratives). As expected, the DUB approach, which is in line with a strong CLT version, was more effective in achieving proficiency in both speaking and writing and equally effective in achieving accuracy.